Developmental Reaction Norms for Water Stressed Seedlings of Succulent Cacti - Rosas, Ulises; Zhou, Royce W.; Castillo, Guillermo; Collazo-Ortega, Margarita (PLOS ONE, 2012)
Succulent cacti are remarkable plants with capabilities to withstand long periods of drought. However, their adult success is contingent on the early seedling stages, when plants are highly susceptible to the environment. To better understand their early coping strategies in a challenging environment, two developmental aspects (anatomy and morphology) in Polaskia chichipe and Echinocactus platyacanthus were studied in the context of developmental reaction norms under drought conditions. The morphology was evaluated using landmark based morphometrics and Principal Component Analysis, which gave three main trends of the variation in each species. The anatomy was quantified as number and area of xylem vessels. The quantitative relationship between morphology and anatomy in early stages of development, as a response to drought was revealed in these two species. Qualitatively, collapsible cells and collapsible parenchyma tissue were observed in seedlings of both species, more often in those subjected to water stress. These tissues were located inside the epidermis, resembling a web of collapsible-cell groups surrounding turgid cells, vascular bundles, and spanned across the pith. Occasionally the groups formed a continuum stretching from the epidermis towards the vasculature. Integrating the morphology and the anatomy in a developmental context as a response to environmental conditions provides a better understanding of the organism's dynamics, adaptation, and plasticity.